Մեծն Արտաշես Առաջինը հայոց պատմության էջերում - Ժորես Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
После Магнеской битвы в 189 г. дo н. э. создание нового независимого государства во главе с Арташесом I (189–160 гг. до н. э.) был решающим для армянской истории. Во времена царя Арташеса I в Армянском нагорье формировалась Великая Армения. Она включала территории от Северного Междуречья до реки Кура, от Атропатены до Софены и Малую Армению. After the battle of Magnessia In 189 B.C. the establishment of new independent state, led by Artashes the First (189–160 B.C.), was a big coup for the Armenian history. At the time of king Artashes the First Great Armenia was formed in the Armenian Highland. It included the area from Northern Mesopotamia to the river Kura, from Atropatene to Sophene and Lesser Armenia.
Keywords: History; Ancient History; D History